Tectonic and climatic controls on the regionally anomalous geomorphic character and behaviour of the Upper Mōtū River, Aotearoa New Zealand - McCord J; Brierley G; Tunnicliffe J; Fuller I; Marden M; Mazengarb C (Elsevier B V, 2025)
Interpreting patterns of landforms is key to geomorphic understandings of landscapes. This study applies Stage One of the River Styles Framework to describe and explain contemporary river character, behaviour and patterns of river types in the Upper Mōtū Catchment on the East Coast of Aotearoa New Zealand. The Mōtū Catchment is regionally anomalous as it stores large volumes of sediment within a perched drainage basin at high elevations in the landscape. Landscape memory exerts a primary control upon contemporary process interactions in the Upper Mōtū Catchment. Geologic and climatic controls upon landscape configuration determine contemporary sediment sources and connectivity relationships, in turn influencing landscape responses to human disturbance and resulting patterns and rates of sediment flux. Tectonic uplift has shaped the relief and valley configuration while the lithological fabric created structural weakness that the river has exploited to form the current drainage pattern. Significant accommodation space has been created on valley floors in the upper catchment. Quaternary climate change instigated phases of valley floor aggradation and reworking that created a complex sequence of river terraces upstream of a knickpoint (Mōtū Falls) in the upper catchment. Terraces now act as confining margins for the laterally adjusting river. Contemporary headcut incision and channel expansion are the dominant contemporary sediment sources in this river system. In contrast to other river systems in the region where targeted revegetation of hillslopes is the key to process-based restoration programmes, bed control structures and a continuous riparian vegetation corridor are required to address sediment issues in the Upper Mōtū Catchment.
Keywords: Valley confinement; Terrace; Landscape pattern; Landscape evolution